Hubungan Pengetahuan dan Sikap Ibu dengan Pemberian Asi Eksklusif di Klinik Bersalin Evie Kec Babalan Kabupaten Langkat Tahun 2022 - Damayanty S; Marta Armita Silaban; Ika Damayanti Sipayung; Ade Rachmat Yudianto (Jurnal Ilmiah Kedokteran dan Kesehatan, 2022)
According to WHO data (2016), the coverage of exclusive breastfeeding worldwide was only around 36% during the 2007-2014 period. The achievement of exclusive breastfeeding in Indonesia in 2016 was 54%, but again decreased in 2017 to only 35% (Ministry of Health RI, 2017). In accordance with Health Law No. 36 of 2009 article 128 paragraph 1 states that every baby has the right to get exclusive breastfeeding from birth for six months except for medical indications and in paragraph (2) it says "during breastfeeding, the family, government, government regions and communities must fully support the baby by providing time and public facilities. Furthermore, in article 200 paragraph 1 it is stated "Everyone who deliberately obstructs the exclusive breastfeeding program as stated in article 128 is subject to imprisonment for 1 year and a maximum fine of Rp. 100,000,000 (one hundred million rupiah). The type of research used is an analytical survey. Analytic survey is research that tries to explore how and why the phenomenon occurs. Then analyze the dynamics of the correlation between phenomena, both between risk factors and effect factors. Test results The results of the chi square statistical test at a confidence level of 0.05 obtained a p value = 0.004 <0.05, then H0 was rejected and Ha was accepted. So it can be concluded that there is a significant relationship between knowledge and exclusive breastfeeding at the Evie Childbirth Clinic Langkat district in 2022. The results of the chi-square statistical test at the 0.05 confidence level obtained a p value = 0.003 <0.05, Ha was accepted. So that it can be concluded that there is a significant relationship between knowledge and exclusive breastfeeding at the Evie Childhood Clinic in Langkat Regency in 2022.